Adenosine and guanosine-based oligonucleotides-loaded PLGA nanoparticles attenuates progression of surgically induced osteoarthritis - Yoonhee Kim; Jin Han; Ji Young Park; Seungwoo Han (Drug Delivery and Translational Research, 2026)
Osteoarthritis (OA) is a chronic degenerative joint disease that lacks effective therapies to halt its progression. While endogenous purinergic signaling—particularly via adenosine—shows promise for reducing inflammation, it is limited by short half-life and off-target effects. To address these limitations, we developed an optimal anti-inflammatory adenosine-guanosine-based oligonucleotide encapsulated in poly(lactic-co-glycolic) acid (PLGA)-based nanoparticles (NanoOligo) to enhance in vivo stability and investigated its impact on surgically induced OA models and the underlying mechanisms responsible for its anabolic effects. A large oligonucleotide library (482 unique 10- to 20-mer sequences) was screened in RAW264.7 macrophages under LPS-induced inflammation to identify the most potent candidate, which was then encapsulated into PLGA nanoparticles using a microfluidic system. NanoOligo significantly protected against cartilage degeneration and alleviated pain behaviors in the rat ACLT + pMx model following intra-articular administration. In IL-1β–treated chondrocytes, it markedly suppressed inflammatory cytokines (TNFα, IL-6) and catabolic proteases (MMP-3, MMP-13, ADAMTS5). Mechanistically, NanoOligo’s anti-catabolic effects were dependent on A1R and A2AR, leading to activation of the PKA–CREB axis and suppression of p38 MAPK signaling, which in turn reduced oxidative stress and cellular senescence via upregulation of the Sirt1–Nrf2–HO-1 antioxidant pathway. Collectively, these findings support joint-localized purinergic modulation as a potential therapeutic target for OA treatment, aligning structural protection with improvements in pain-related behaviors. Graphical abstract Schematic of the proposed mechanism of action for the adenosine–guanosine-based oligonucleotide, via the A1R- and A2AR-mediated PKA–CREB axis and Sirt1–Nrf2–HO-1 pathway. The oligonucleotide is thought to release adenosine (Ad) and guanosine (Gu) moieties that bind to A1R and A2AR on the cell surface. Receptor activation increases intracellular cAMP levels, thereby stimulating PKA. Subsequently, the Sirt1–Nrf2–HO-1 and CREB antioxidant pathways are activated, reducing ROS levels. This decline in ROS feeds back to prematurely terminate p38 MAPK activation, a key driver of catabolic processes in OA. As a result, MMP-13 expression is diminished, ultimately preserving extracellular matrix integrity.

DDT exposure induces microglial activation and disease-associated microglial signatures: Relevance to mechanisms of Alzheimer’s disease - Isha Mhatre-Winters; Aseel Eid; Nicole Blum; Yoonhee Han; Ferass M. Sammoura; Long-Jun Wu; Jason R. Richardson (NeuroToxicology, 2025)